Preserved slow conducting corticomotoneuronal projections in amyotrophic lateral sclerosis with autosomal recessive D90A CuZn-superoxide dismutase mutation - Weber, Markus; Eisen, Andrew; Stewart, Heather G.; Andersen, Peter M. (Brain (London, England : 1878), 2000)
Recently, a subgroup of the amyotrophic lateral sclerosis (ALS) syndrome associated with mutations in the gene encoding the free radical scavenging enzyme CuZn-superoxide dismutase (CuZn-SOD, SOD1) has been identified. Some 67 different mutations have been reported worldwide to date, comprising about one-fifth of familial ALS cases in the populations studied. The autosomal recessively inherited D90A CuZn-SOD mutation has been associated with a very slowly progressive, clinically distinct phenotype, and is neurophysiologically characterized by very slow central motor conduction. It is not known which physiological and/or biochemical mechanisms are responsible for the different clinical course. To delineate ALS associated with this particular CuZn-SOD mutation from ALS without mutations, we performed a detailed neurophysiological study of the corticomotoneuronal function using peristimulus time histograms (PSTHs) in eight ALS patients homozygous for the D90A CuZn-SOD mutation. The results were compared with those obtained in 12 non-hereditary ALS patients and 11 healthy subjects. PSTHs were constructed from three to seven different, voluntarily recruited motor units of the extensor digitorum communis muscle (EDC) in each patient. The onset latency, number of excess bins, duration and synchrony of the primary peak were analysed. All measurements differed significantly between healthy controls and the D90A patients (P < 0.0007). The mean onset latency of the primary peak in D90A patients was 35.3 ms, compared with 24.2 ms for non-hereditary ALS patients and 19.3 ms for normal subjects (P < 0.0000). Delayed primary peaks in the D90A patients were desynchronized and characteristically preceded by a marked suppression phase. This suppression phase was not seen in non-hereditary ALS patients. We conclude that the mainly slow conducting and/or polysynaptic corticomotoneuronal connections are preserved in the D90A homozygous cases, and that the cortical and possibly spinal inhibitory circuitry is preserved. These events may partially protect the motor neurons, slowing down the degenerative process.